First-Time Diagnosis After an Emergency Presentation in Children With Cancer. Issue 2 (12th February 2022) - Schiavetti, Amalia; Aliotti Lippolis, Maria; Gentile, Isotta; De Grazia, Alessandra; Ferrara, Eva; Bonci, Enea
Abstract : Aim: To determine the prevalence rate of cancer diagnoses by an emergency route, the related risk factors and whether the emergency diagnosis was associated with poorer outcome. Methods: Retrospective observational study with identification of patients diagnosed at the Pediatric Oncology Unit of "Sapienza" University between 2008 and 2018. The percentage of patients who received a first-time diagnosis after an emergency presentation was determined. Two-year survival and clinical factors, such as sex, age and histology, associated to emergency presentation were evaluated. Results: Of 207 patients (109 girls and 98 boys; median age, 120 months), with a first-time diagnosis of solid tumor, 5.8% were diagnosed during an emergency admission after a median latency time of 2.5 days. Cases with an emergency diagnosis were younger compared with those who were diagnosed electively (median age, 30 months vs 120 months, P < 0.005). Higher prevalence rate of emergency presentation was detected in patients with lymphoma compared with those with no lymphoma disease (28.6% vs 4.1%; P < 0.0001). All patients were managed to overcome their emergency presentation, 33.3% of these died later. No statistically significant difference for 2-year overall survival was found between patients with an emergency diagnosis and those with elective diagnosis (66.7% vs 81.0%; odds ratio, 2.1; confidence interval, 0.6–7.5; P = 0.22). Conclusions: A minor but not negligible number of pediatric patients come to a first-time diagnosis of cancer as result of a life-threatening event; risk factors were younger age and lymphoma disease. The emergency event can be successfully treated, and it was not related to a poorer survival.